Persuasion, Face-Threatening Acts, and Mitigation Strategies in Southeast Nigeria Haggling Encounters - Justus Chidi Ugwu; Elizabeth Ebere Agbo; Obiageli Cynthia Nnamani (Indonesian Journal of English Language Studies (IJELS), 2025)
Given the fact that haggling could provide the opportunity for deceit,the seller employs different persuasive strategies to convince the, already alerted, buyer to patronise them. However, despite such persuasive strategies, there could be communication breakdown because of distrust and suspicion among the interactants. Such communication breakdown requires a repair for a successful haggling encounter.This study looks at the main artistic modes and pragmatic strategies of persuasion used in southeast Nigerian markets to identify the pragmatic techniques that are used to mitigate threatened face in market encounters. The data consist of ninety sampled haggling experiences involving wholesalers (15), retailers (15), apprentices (15), and customers (45), taken from the five states that comprise Southeast Nigeria. The data analysis draws on Aristotle's threefold method of persuasion, paying close attention to the pathos and logos of his rhetorical appeals, and Mey’s (2001) theory of pragmatic acts.  The analysis shows that there is strong presence of logos in the data, with a predomination of the pathos component of the rhetorical appeals. The research also indicates that while face-threatening acts are practed through questioning, comparing, and doubting, it is also mitigated through apologising, euphemising and blame transfer.